Multiply it!

Algebra Level 2

A = 1 3 + 1 3 2 + 1 3 3 + + 1 3 8 = ? \displaystyle \large{A =\frac{1}{3} +\frac{1}{3^{2}} + \frac{1}{3^{3}} + \ldots + \frac{1}{3^{8}}} = \ ?

3 3 1 3 \frac13 6560 6561 \frac{6560}{6561} 3280 6561 \frac{3280}{6561}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Omkar Kulkarni
Jan 2, 2015

A = 1 3 + 1 3 2 + 1 3 3 + . . . + 1 3 8 A = \frac {1}{3} + \frac {1}{3^{2}} + \frac {1}{3^{3}} + ... + \frac {1}{3^{8}}

= 1 3 + 1 3 ( 1 3 + 1 3 2 + . . . + 1 3 7 ) = \frac {1}{3} + \frac {1}{3} ( \frac {1}{3} + \frac {1}{3^{2}} + ... + \frac {1}{3^{7}} )

= 1 3 + 1 3 ( 1 3 + 1 3 2 + . . . + 1 3 7 + 1 3 8 1 3 8 ) = \frac {1}{3} + \frac {1}{3} ( \frac {1}{3} + \frac {1}{3^{2}} + ... + \frac {1}{3^{7}} + \frac {1}{3^{8}} - \frac {1}{3^{8}} )

= 1 3 + 1 3 ( A 1 3 8 ) = \frac {1}{3} + \frac {1}{3} ( A - \frac {1}{3^{8}})

A = 1 3 + 1 3 ( A 1 3 8 ) \therefore A = \frac {1}{3} + \frac {1}{3} ( A - \frac {1}{3^{8}})

3 A = 1 + A 1 3 8 3A = 1 + A - \frac {1}{3^{8}}

2 A = 1 1 6561 2A = 1 - \frac {1}{6561}

2 A = 6560 6561 2A = \frac {6560}{6561}

A = 3280 6561 \boxed {A = \frac {3280}{6561}}

Very good! A very dynamic visual explanations by using factoring out and best of all i like the way you used1/3^8 -1/3^8 which didn't affect the value! You're only 16 of age so you must be a genius! High hat to you!

Allan Lindo - 5 years, 10 months ago

Log in to reply

Hahaa :D Thanks!

Omkar Kulkarni - 5 years, 10 months ago

A = 1 3 + 1 3 2 + 1 3 3 + . . . + 1 3 8 = 1 3 ( 1 + 1 3 + 1 3 2 + . . . + 1 3 7 ) \displaystyle A = \frac{1}{3} + \frac{1}{3^2} + \frac{1}{3^3} +...+ \frac{1}{3^8} = \frac {1}{3} \left( 1 + \frac{1}{3} + \frac{1}{3^2} +...+ \frac{1}{3^7} \right)

= 1 3 n = 0 7 ( 1 3 ) n = 1 3 ( 1 ( 1 3 ) 8 1 1 3 ) = 1 2 ( 3 8 1 3 8 ) \displaystyle \quad = \frac {1}{3} \sum _{n=0}^7 {\left( \frac{1}{3} \right)^n} = \frac {1}{3} \left( \frac{1-\left( \frac{1}{3} \right)^8}{1 - \frac{1}{3}} \right) = \frac {1}{2} \left(\frac {3^8-1} {3^8} \right)

= 1 2 ( 6561 1 6561 ) = 3280 6561 \displaystyle \quad = \frac {1}{2} \left(\frac {6561-1} {6561} \right) = \boxed{\dfrac {3280}{6561}}

Kanagaraj N.N
Aug 14, 2015

A is the sum of the Geometric series with the common ratio (r = 1/3). We can use the below formula to compute the sum

      A = a(1-r^n)/(1-r)

where

a  = first term         =    1/3

r  = common ratio       =    1/3

n  = number of terms    =     8

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...